Ancestral polymorphism and recent invasion of transposable elements in Drosophila species - Dias, Elaine Silva [UNESP]; Aparecida Carareto, Claudia Marcia [UNESP] (Biomed Central Ltd., 2012)
Background: During the evolution of transposable elements, some processes, such as ancestral polymorphisms and horizontal transfer of sequences between species, can produce incongruences in phylogenies. We investigated the evolutionary history of the transposable elements Bari and 412 in the sequenced genomes of the Drosophila melanogaster group and in the sibling species D. melanogaster and D. simulans using traditional phylogenetic and network approaches.Results: Maximum likelihood (ML) phylogenetic analyses revealed incongruences and unresolved relationships for both the Bari and 412 elements. The DNA transposon Bari within the D. ananassae genome is more closely related to the element of the melanogaster complex than to the sequence in D. erecta, which is inconsistent with the species phylogeny. Divergence analysis and the comparison of the rate of synonymous substitutions per synonymous site of the Bari and host gene sequences explain the incongruence as an ancestral polymorphism that was inherited stochastically by the derived species. Unresolved relationships were observed in the ML phylogeny of both elements involving D. melanogaster, D. simulans and D. sechellia. A network approach was used to attempt to resolve these relationships. The resulting tree suggests recent transfers of both elements between D. melanogaster and D. simulans. The divergence values of the elements between these species support this conclusion.Conclusions: We showed that ancestral polymorphism and recent invasion of genomes due to introgression or horizontal transfer between species occurred during the evolutionary history of the Bari and 412 elements in the melanogaster group. These invasions likely occurred in Africa during the Pleistocene, before the worldwide expansion of D. melanogaster and D. simulans.
Keywords: Transposable elements; Ancestral polymorphism; Horizontal transfer; Introgressive hybridization; Recent invasion; Drosophila melanogaster group